THE INFLUENCE OF AUDITOR PROFESSIONALISM AND ETHICAL ORIENTATION AGAINST WHISTLEBLOWING AT BPKAD PALOPO CITY - Amal, Muh. Ikhlasul; Syamsuddin, Soyfan; Rusli, Andika (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
Abstract The purpose of this research is to evaluate the impact of auditor professionalism and ethical orientation on whistleblowing behavior at the Regional Financial and Asset Management Agency (BPKAD) of Palopo City. The research uses a quantitative method with the entire population of auditors and employees at the BPKAD of Palopo City. The sample was taken using the purposive sampling method, and data was collected through structured questionnaires. Data were described using SPSS software, and multiple linear regression was used to analyze the data. The research findings indicate that auditor professionalism and ethical orientation, both partially and simultaneously, have a positive and significant impact on whistleblowing behavior. These findings indicate that the enhancement of auditor professionalism and employee ethical orientation can encourage the creation of a more effective violation reporting culture within the local government environment. The implication of this research is the need for training programs to enhance auditors' competencies and the dissemination of ethical values in the workplace. In addition, regulations and protections for whistleblowers need to be strengthened so that employees feel safe reporting violations.